Efek Firm Size, Profitability, Gearing Ratio, Dan Public Ownership Terhadap Risk Disclosure - Susanto Salim, Sachita Vamia Sudharto, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
This study aims to analyze the effect given by firm size, profitability, gearing ratio and public ownership on risk disclosure. This study used purposive sampling as the sampling technique and SPSS version 25 is used as data processing software. There are 117 data from 39 samples of non-cyclical companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2020 period used in this study. The results show that firm size has a positive and insignificant effect on risk disclosure, while profitability has a positive and significant effect on risk disclosure, gearing ratio has a positive and insignificant effect on risk disclosure and public ownership has a positive and significant effect on risk disclosure.